Village Baseline Study: Site Analysis Report for Segou – Cinzana, Mali (MA0109) - Goudou D; Traoré Gue, J.N.; Ouédraogo, Mathieu; Segda, Zénabou; Diakite, L.; Kebe Z; Diarra, Camaram Aichatou; Zougmoré, Robert B.; Moussa, Abdoulaye S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
The village baseline study of Tongo village in the CCAFS benchmark site of Cinzana, Mali took place from 12 to 14 July 2011. Focus group discussions were conducted separately for men and women. The village has an abundance of natural resources such as savannah, grassland, ponds, farmlands and several kinds of socio-economic infrastructure. Some of the natural resources, however, are in a state of progressive degradation due to increase in human population; indiscriminate felling of trees; clearing of forests and deforestation; lack of rainfall; drought; and animal pressure.